A novel thiazole based acceptor for fullerene-free organic solar cells. (February 2018) - Mahmood, Asif; Hu, Junyi; Tang, Ailing; Chen, Fan; Wang, Xiaochen; Zhou, Erjun
Abstract: In this work, an electron-withdrawing thiazole ring is used as a bridged unit in the design of the small molecular electron acceptor. The new electron acceptor, namely DC-IDT2Tz, was designed with indacenodithiophene as core and 1, 1-dicyanomethylene-3-indanone as end-capped unit, and thiazole ring as spacers. Compared with the thiophene spacer, the thiazole bridge exhibited blue-shifted absorption and deep energy levels, which provides more complementary absorption and large diving-force for the exciton dissociation. Besides it has remained some advantages of the thiophene linked acceptors, such as strong and board absorption in visible light region and planate backbone. The device based on PTB7-Th as the donor material and DC-IDT2Tz as the acceptor material exhibited a high PCE of 5.81%. Graphical abstract: